The Effect of Managerial Bias on Employees' Specific Human Capital Investments - WANG, Heli (Institutional Knowledge at Singapore Management University, 2012)
Contrary to the conventional belief that escalation of commitment by managers is detrimental, this study argues for its potential benefits. While firm-specific human capital is considered a critical element of knowledge-based resources that have the potential for superior firm performance, factors affecting the incentives for employees to make such investments are often overlooked. In the case of firms taking on risky projects, fear of project termination often reduces employees’ incentives to make specific human capital investments. We argue that in this situation, the firms may find it desirable to commit to a lower probability of project termination in order to encourage the development of specific human capital by employees. Managers’ escalation of commitment tendency may function as such a commitment mechanism. We find support for the key argument from the results of two experimental studies.